Spin switching in tris(8-aminoquinoline)iron(ii)(BPh4)2: quantitative guest-losing dependent spin crossover properties and single-crystal-to-single-crystal transformation. Issue 1 (5th December 2018) - Yang, Feng-Lei; Chen, Xin; Wu, Wen-Hao; Zhang, Jing-Hang; Zhao, Xiang-Mei; Shi, Yan-Hui; Shen, Fei
Abstract : Compound tris(8-aminoquinoline)Fe(ii )(BPh4 )2 ·2(MeCN) displayed quantitative spin crossover properties with further occurrence of single-crystal-to-single-crystal transformation. Abstract : As a derivative of 2-picolylamine, which contains rich protons favouring hydrogen bond formation to assemble a variety of valuable spin crossover (SCO) compounds, 8-aminoquinoline (aqin) will be a good candidate for constructing new mononuclear bistable state compounds. With the guidance of this view, two solvated compounds [Fe(aqin)3 ](BPh4 )2 ·2(CH3 CN) (1·2CH3 CN ) and [Fe(aqin)3 ](BPh4 )2 ·1.5(CH3 COCH3 ) (2·1.5CH3 COCH3 ) were synthesized. The structural characterization and magnetic studies demonstrate that this strategy has been successful. Single-crystal diffraction reveals that both the mononuclear compounds have facial ( fac -)-configuration cations, which form hydrogen bonds using –NH2 groups with solvent molecules (acetonitrile or acetone). Subsequent magnetic measurement shows the highly sensitive solvent-dependent occurrence of a spin transition above room temperature for both compounds. Interestingly, for compound1·2CH3 CN, in the successively repeated heating and cooling process, by monitoring the loss of solvent molecules by TGA, the shifting of the spin transition curve is found to be linearly dependent on the fraction of the residual solvent content. Additionally, the desolvated sample can re-solvate with CH3 CN and recover the magnetic response reproducibly. Furthermore, after losing the acetonitrile molecules, the single-crystal-to-single-crystal transformation occurred to give1 .